Immune‐responsive biodegradable scaffolds for enhancing neutrophil regeneration. Issue 1 (19th April 2022) - Kerr, Matthew D.; McBride, David A.; Johnson, Wade T.; Chumber, Arun K.; Najibi, Alexander J.; Seo, Bo Ri; Stafford, Alexander G.; Scadden, David T.; Mooney, David J.; Shah, Nisarg J.
Abstract: Neutrophils are essential effector cells for mediating rapid host defense and their insufficiency arising from therapy‐induced side‐effects, termed neutropenia, can lead to immunodeficiency‐associated complications. In autologous hematopoietic stem cell transplantation (HSCT), neutropenia is a complication that limits therapeutic efficacy. Here, we report the development and in vivo evaluation of an injectable, biodegradable hyaluronic acid (HA)‐based scaffold, termed HA cryogel, with myeloid responsive degradation behavior. In mouse models of immune deficiency, we show that the infiltration of functional myeloid‐lineage cells, specifically neutrophils, is essential to mediate HA cryogel degradation. Post‐HSCT neutropenia in recipient mice delayed degradation of HA cryogels by up to 3 weeks. We harnessed the neutrophil‐responsive degradation to sustain the release of granulocyte colony stimulating factor (G‐CSF) from HA cryogels. Sustained release of G‐CSF from HA cryogels enhanced post‐HSCT neutrophil recovery, comparable to pegylated G‐CSF, which, in turn, accelerated cryogel degradation. HA cryogels are a potential approach for enhancing neutrophils and concurrently assessing immune recovery in neutropenic hosts.